USE OF THIAZIDE DIURETICS IN THE MANAGEMENT OF CENTRAL DIABETES INSIPIDUS IN A NEONATE - H, Haiza Hani; L, Annie; T, Pian Pian; T, Sze Teik; WSL, Jeanne; MS, Nalini; YH, Janet Hong (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION The treatment of central diabetes insipidus (DI) with Desmopressin in the neonatal period is challenging because of the significant risk of hyponatremia. The fixed anti-diuresis action of Desmopressin and the obligate high fluid intake with milk feeds may lead to considerable risk of water intoxication and hyponatremia in neonates. Few case reports described the use of thiazide diuretics for treatment of central DI in infancy which was switched to Desmopressin later in life. METHODOLOGY We present a case of a premature female baby with midline defect, central DI and poor weight gain. RESULTS She was started with oral hydrochlorothiazide dose of 0.5 mg per kg per dose two times daily. Throughout the hospital stay, the dose was adjusted to 0.48 mg per kg per dose twice daily to achieve a stabilized serum sodium values ranging between 140-145 mmol/L. She has no obvious complications of hyponatremia. She was thriving well during follow up. CONCLUSION Oral thiazide diuretics is an alternative treatment of central DI in neonates. It is effective to achieve adequate control of DI without wide serum sodium fluctuations.